1021 Retrospective study of the prevalence of skin and subcutaneous diseases in brazilian workers receiving sick leave benefits. (24th April 2018) - Rosa, NDA; Macedo, IF; Leal, MS; Galhardi, CM; Dias Junior, AF; Ferreira, LR
Abstract : Introduction: Dermal exposure to hazardous agents can result in a variety of occupational diseases, including occupational skin diseases (OSD), which is characterised by skin alterations related to the work, and may be related to the lack of use of individual protective equipment. The objective of this study is to identify the prevalence of OSD in the worker's population and the relation with the working conditions. Methods: This was a cross-sectional study (November 2012 until February 2017) involving 49.391 employees receiving sick leave benefits from the Brazilian National Institute of Social Security. From these data, it was selected the cases related to occupational skin diseases including: gender, age, main occupation, harzard exposure and the international classification of diseases (ICD-10) codes to work-related skin lesions. Results: The study revealed that the OSD was present in 493 workers. The most prevalent dermatoses were skin and subcutaneous infection diseases (ICD L00-L08) in 216 workers. Followed by other skin and subcutaneous diseases (CID L80-L99) in 129 patients, 60 patients were diagnosed as skin accessory structures diseases (CID L60-L75) and dermatitis with ICD (L10-L30). The results showed that the participants were 55% female having a mean age of 39 y/o; The main occupational posts associated with OSD were agricultural workers (32%), health workers (22%) cleaning personnel (15%) and administrative employees (11%). Aproximatelly 68% of the workers had related some contact with chemicals agents. Conclusion: The study confirmed the meaningful influence of OSD on the work absence specially in agricultural and health workers, and this occurrence may be related to skin disease infections, and other skin and accessory skin diseases among these workers. Furthermore, the work-related skin diseases may be a result of inappropriate use of individual protection equipment as well as the worker exposure to the chemicals and other trigger factors.